PELAKSANAAN UPAYA PENCEGAHAN PENCEMARAN LAUT YANG DISEBABKAN LIMBAH KAPAL DI WILAYAH KEPULAUAN RIAU OLEH KESATUAN PENJAGAAN LAUT DAN PANTAI (KPLP) TANJUNGUBAN BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2008 TENTANG PELAYARAN - Bima Sakti Zalvadeora; Erdianto Effendi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Water pollution is a form of environmental pollution and one of the factors is the disposal of waste by ships at sea. The level of marine pollution in the Riau Islands Province is increasingly alarming. The Riau Islands Province Sea has been proven to be polluted by the presence of waste findings on the coast and the implementation of patrols by the authorities. But the difficulty of patrolling in the vast archipelago and directly bordering the neighboring country has made it difficult to enforce the law. Tanjung Uban Class II Sea and Coast Guard Unit as a law enforcement officer in terms of enforcement is still slow, due to the difficulty of conducting patrols and the lack of a patrol fleet. In addition, Riau Islands Province has an Office of the Environment and Forestry which has the duty as a supervisor and implementing law enforcement. The purpose of writing this thesis, namely First to find out how the implementation of prevention of marine pollution caused by ship waste by the Sea and Coast Guard Unit based on the Riau Islands region. Secondly, to find out the obstacles in preventing marine pollution caused by ship waste in the Riau Islands region. Third, to find out the efforts made to overcome obstacles in preventing sea pollution in the Riau Islands region.This type of research can be classified as sociological research. The research locations were the Department of Environment and Forestry of the Riau Islands Province and the Sea and Coast Guard Unit of Tanjung Uban Class II. Data sources used are primary data and secondary data. Data collection techniques are interviews, questionnaires and literature study. After the data collected is then analyzed qualitatively using the deductive method that is drawing conclusions from things that are general to things that are specific.Keywords : Prevention - Environmental Pollution - Sea Islands, Riau - Ship waste